A new world of gold and silver - TePaske, John J. (John Jay), 1929-2007 (Atlantic world (Leiden, Netherlands), 2010)
Colonial Latin America was famed for the precious metals plundered by the conquistadores and the gold and silver extracted from its mines. Historians and economists have attempted to determine the amount of bullion produced and its impact on the colonies themselves and the emerging early-modern world economy. Using official tax and mintage records, this book provides decade-by-decade and often annual data on the amount of gold and silver officially refined and coined in the treasury and mint districts of Spanish and Portuguese America. It also places American bullion output within the context.